Papel do exercício físico associado a diferentes Inibidores da Enzima de Conversão da Angiotensina (iECA) sobre o fator de crescimento endotelial de vasos – VEGF e angiogênese em ratos espontaneamente hipertensos e normotensos - Macedo, Anderson Geremias (Universidade Federal de São Carlos, 2017)
Hypertension (HA) is a complex and multifactorial disease, considered as an important risk factor for cardiovascular diseases. It is known that high blood pressure (BP) levels are maintained by increased Total peripheral resistance (TPR). Among the factors that contribute to the maintenance of high TPR, there are arterioles remodeling and rarefaction, which occurs in several tissues. Physical training (T) has been considered as an important adjunct to pharmacological treatment in the control and treatment of HA. In this sense, exercise has been effective in improving vascular remodeling and promoting angiogenesis. Among the pharmacological therapies used clinically, angiotensin II converting enzyme inhibitors (ACEi) have shown great effectiveness, mainly by reducing mortality. It has been suggested that due to some different biochemical and pharmacological characteristics between captopril and perindopril, there may be some differential effect on T-induced angiogenesis. It has been demonstrated that captopril may inhibit T-induced angiogenesis after acute exercise, but almost nothing is known about it effects after chronic exercise. Therefore, the objective of this study was to compare the effects of the chronic use of captopril and perindopril on angiogenesis induced by T in normotensive and spontaneously hypertensive rats and to investigate some of the possible mechanisms involved in these alterations. For this purpose, 48 normotensive Wistar rats and 48 spontaneously hypertensive rats (SHR) underwent T protocol (60% maximum physical capacity, for 8 weeks) or maintained sedentary. During the last 6 weeks, the animals were treated with captopril (25 mg / kg per day, i.p.) or perindopril (3 mg / kg per day, gavage) and the control animals received water. Body weight and baseline values of systolic blood pressure (SBP), diastolic blood pressure (DBP), mean (MAP) and heart rate (HR) were analyzed. The anterior tibial muscle (TA) and myocardium were removed for the morphometric analyzes of the capillary / fiber ratio (C: F) and analyzes of the protein production of vascular endothelial growth factor (VEGF), its receptor (VEGFR-2) and enzyme endothelial nitric oxide synthase (eNOS). As expected, the values of SBP, DBP and MAP were higher in the sedentary SHR (+ 30%, + 33% and + 32%, for SBP, DBP and MAP respectively) when compared to sedentary Wistar. Both T and pharmacological treatments reduced BP values by a similar magnitude. The C:F ratio in TA was reduced in all sedentary SHRS compared to sedentary Wistar, and this reduction was associated with lower levels of VEGF (~ -26%) and eNOS (~ -27%). Training increased C:F ratio in trained Wistar rats compared to sedentary Wistar because of increased production of VEGFR-2 (+ 17%) and eNOS (+ 31%). In addition, T prevented TA rarefaction in SHRs, mainly by preventing reductions in VEGF and eNOS production. Chronic treatment with captopril or perindopril significantly attenuated angiogenesis in Wistar animals, although this effect was greater after treatment with captopril (-19%) when compared to perindopril (-13%). In the SHR animals, perindopril did not attenuate T-induced angiogenesis. On the other hand, captopril attenuated this effect (18%). This response occurred due to normalization of eNOS levels after PT in trained Wistar and SHR rats treated with perindopril alone. The myocardial C: F ratio was reduced in all sedentary SHR compared to sedentary Wistar. T increased myocardial C: F ratio in trained Wistar rats (~ + 14%) in all groups compared to sedentary ones. Similarly, T increased C: F ratio in trained SHR compared to sedentary SHR and normalized to number of vessels compared to sedentary Wistar. This response was also mediated by increased production of eNOS in all trained groups. These findings allow us to conclude that T promoted angiogenesis in skeletal and cardiac musculature and chronic use of ACE inhibitors attenuated this response in the skeletal muscle, and perindopril did not attenuate T-induced angiogenesis in hypertensive animals. In this way perindopril may be suggested as the best drug of choice for hypertensive patients who do exercise.
Keywords: Treinamento físico; Hipertensão arterial; Microcirculação; Perindopril; Captopril; Músculo esquelético; Physical training; Hypertension; Microcirculation; Skeletal muscle; CIENCIAS BIOLOGICAS::FISIOLOGIA